2017
DOI: 10.1007/s10517-017-3963-z
|View full text |Cite
|
Sign up to set email alerts
|

Complex Analysis of Diffusion Transport and Microstructure of an Intervertebral Disk

Abstract: We studied the relationship between diffusion transport and morphological and microstructural organization of extracellular matrix of human intervertebral disk. Specimens of the lumbar intervertebral disks without abnormalities were studied ex vivo by diffusion-weighed magnetic resonance imaging, histological and immunohistochemical methods, and electron microscopy. Distribution of the diffusion coefficient in various compartments of the intervertebral disk was studied. Significant correlations between diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“… 12 , 13 Lastly, degeneration of the IVD leads to changes in the NP's ECM that altered diffusion kinetics of solutes through the IVD. 14 , 15 , 16 As a result of the changes in IVD biology, diffusion rates decrease dramatically, leading to poor nutrition (ie, glucose and oxygen), high acidity, and high cell death. 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 , 13 Lastly, degeneration of the IVD leads to changes in the NP's ECM that altered diffusion kinetics of solutes through the IVD. 14 , 15 , 16 As a result of the changes in IVD biology, diffusion rates decrease dramatically, leading to poor nutrition (ie, glucose and oxygen), high acidity, and high cell death. 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 …”
Section: Introductionmentioning
confidence: 99%
“…12,13 Lastly, degeneration of the IVD leads to changes in the NP's ECM that altered diffusion kinetics of solutes through the IVD. [14][15][16] As a result of the changes in IVD biology, diffusion rates decrease dramatically, leading to poor nutrition (ie, glucose and oxygen), high acidity, and high cell death. [17][18][19][20][21][22][23][24][25][26][27][28][29][30] In addition, clinical stem cell studies reported widely varying cell doses being administered to treat IVD degeneration, ranging from 1 million to 40 million cells per patient as reviewed by Sakai and Schol.…”
mentioning
confidence: 99%
“…4 Based on these efforts, spinal traction does not appear to address nutrient deprivation, requiring innovative new therapies for degeneration. 49 Work by Fields et al explored how changing CEP permeability would influence nutrient diffusion -though nutrient delivery was not clearly improved, this study established a clear correlation. 50 Therefore, this strategy offers a promising new direction for addressing nutrient transport deficits in IVD.…”
Section: Nutrient Considerations In Ivd Therapymentioning
confidence: 71%
“…An IVD is a fibro-cartilaginous joint consisting of the outer concentric cartilaginous lamellae of the annulus fibrosus and an inner deformable proteoglycan-rich nucleus pulposus centered between two cartilage endplates and their connected vertebrae [ 75 , 76 , 77 ]. IVD herniation is the avulsion of the nucleus pulposus through a ruptured annulus fibrosus.…”
Section: Resultsmentioning
confidence: 99%